Use of MRI Image Recording of the Recitation of Surah al-Fatihah Towards the Makhraj of Letters: A Study on Quran Teachers at Kelantan Islamic Foundation School - Mohd Najib Shukri Saghiri; Mohd Zaini Zakaria; Dr. Fadzidah Mohd Idris; Sharifah Najwa Syed Mohamad; Mohd Zamrus Mohd Ali (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Surah al-Fatihah is one of the earliest and simplest surahs recited in Muslim prayers, and is widely used by Quran teachers to teach the accurate articulation and makhraj of Hijaiyyah letters. However, in Malaysia, the application of medical devices to study anatomical movements during Quranic recitation remains limited. Objective : To determine the level of knowledge among Quran teachers from selected Islamic schools in Malaysia and assess the suitability of using MRI image recordings to teach makhraj of letters based on the Integration of Naqli and Aqli (INAQ) approach. Research Methods / Implementation Methods : A total of 40 Islamic schools will be selected through convenience sampling involving an estimated 120 Quran teachers. The study adopts a mixed-method approach combining qualitative and quantitative data. MRI recordings used in this study were developed collaboratively by researchers at Universiti Sains Islam Malaysia (USIM) and Universiti Sains Malaysia (USM). Results : The study is expected to demonstrate that MRI image recordings can serve as an effective and innovative teaching aid to enhance Quranic instruction, particularly in articulating correct makhraj of letters. Conclusion / Lesson Learned : Findings are anticipated to support the use of MRI image recordings as a classroom teaching tool for Quran teachers in various schools. The technique also has the potential to be expanded to the Islamic Education Division (BPI), Ministry of Education Malaysia (KPM).